Low compliance to post‐screening recommendations in a family‐based Helicobacter pylori screening and treatment program: A prospective cohort study. Issue 5 (11th July 2022) - Kong, Qingzhou; Li, Yueyue; Li, Ruili; Li, Zhiyuan; Zheng, Xueting; Wang, Zhi; Song, Kun; Zhang, Xia; Liu, Jing; Han, Zhongxue; Duan, Miao; Ding, Yuming; et al.
Abstract: Background: Intra‐family transmission is an important Helicobacter pylori ( H. pylori ) infection route. Family‐based screening and treatment of H. pylori is a promising strategy. However, limited data are available on patient compliance with post‐screening recommendations for such a strategy. Materials and Methods: A prospective cohort study of families from six regions in Shandong, China, from July 2021 to February 2022 was conducted. Demographic characteristics, prior testing, and treatment for H. pylori, prior gastroscopy, symptoms, and family history were collected. Infection status of participants was determined using the 13 C‐urea breath test. Infected participants were recommended to undergo eradication treatment, confirmation testing, and gastroscopy per expert consensus. Participants were monitored for 6 months to record recommendation compliance in a real‐world setting. Logistic regression models were used to analyze the factors influencing compliance with the recommendations. Results: The study included 1173 individuals from 386 families with the overall infection rate of 36.7%. The recommendation compliance for eradication treatment, confirmation testing, and gastroscopy was 69.3% (271/391), 32.5% (88/271), and 6.1% (19/309), respectively. Factors that increased the risk of lower compliance were male sex (odds ratio [OR], 1.917, 95% confidence interval [CI], 1.233–2.981), and living in a non‐urban area (OR, 1.954, 95% CI, 1.241–3.074), for treatment recommendations; having more than one infected family member (OR, 2.138, 95% CI, 1.237–3.698), and a lower family income (¥100, 000–¥300, 000 per year, OR, 7.247, 95% CI, 1.788–29.363; or <¥100, 000 per year, OR, 7.294, 95% CI, 1.832–29.042), for confirmation testing recommendations; and being asymptomatic (OR, 3.009, 95% CI, 1.105–8.196), for gastroscopy recommendations. Conclusions: Post‐screening recommendation compliance for this family‐based H. pylori screening and treatment program was unsatisfactory. Further studies focusing on pre‐screening education are warranted to improve compliance.